Clinical and prognostic role intensification of apoptosis in patients with arterial hypertension and chronic obstructive pulmonary disease - Tyaglaya, O. S.; Тягла, Оксана Сергіївна (Wloclawek : Izdevnieciba «Baltija Publishing», 2018)
Introduction. It is known that both chronic obstructive pulmonary disease (COPD) and arterial hypertension (AH) are multifactorial diseases, and develop as a result of a complex interaction of genetic and environmental factors. The purpose of this study was to study the metabolism of caspase-7 and caspase-9 in patients with chronic obstructive pulmonary disease (COPD) in combination with arterial hypertension (AH).